Historical, ecological, and governance aspects of intensive forest biomass harvesting in Denmark. Issue 5 (21st March 2016) - Stupak, Inge; Raulund‐Rasmussen, Karsten
Abstract : Intensive forest harvesting has increased in Fennoscandia over the last few decades. Similar developments may follow throughout Europe as renewable energy replaces fossil fuels. The international literature suggests that intensive harvesting could increase ecological risks to yield, carbon stores, soil fertility, and biodiversity, but geographically specific knowledge is sparse in many countries, and results do not extend beyond 5–30 years after harvesting. We use Denmark as a case for discussing future directions. Forest history is described, and research on ecological effects and their inclusion in governance is reviewed. Denmark was almost completely deforested by the early 1800s, but centuries of afforestation have resulted in a current forest cover of 14.3%. Research commonly uses stem‐only harvesting as a reference against which to compare intensive harvesting impacts, but pristine forests would be a more useful reference for ecological processes and biodiversity. However, pristine forests are almost non‐existent in Europe, and non‐intervention, self‐regulating forests provide an alternative. Governance and positions of non‐governmental organizations in Denmark focus more on general forest management impacts and conservation of light‐demanding biodiversity associated with historic coppicing and grazing than on intensive harvesting. The energy sector drives the development of new governance to verify forest biomass sustainability, but the national knowledge base for such verification is limited. As part of a larger solution, we suggest establishing a network of non‐intervention, self‐regulating forests that can serve as a reference for long‐term research and monitoring of intensive harvesting impacts. This would support the application of adaptive management strategies, and continuous improvements of best management practice guidelines. WIREs Energy Environ 2016, 5:588–610. doi: 10.1002/wene.206 This article is categorized under: Bioenergy > Economics and Policy Bioenergy > Climate and Environment Energy and Development > Climate and Environment Abstract :